(untitled) (International Journal of Engineering and Computer Science, 2014)
In this color mixing machine we use three tanks which are of Red, Blue and Yellow. The three tanks consist of level sensor and fitted with hydraulic line. The hydraulic line consist of solenoid valve.The tank consists of color Steiner of Red, Blue and Yellow. The Steiner flows from hydraulic line into the mixing tank through solenoid valve. The solenoid valve is a digital output device that is connected to the PLC .Their is three solenoid valves connected to three tanks. The white color tint is in which is tank 4 of required proportion (as per order). The weight of the mixing tank is calculated by a weight measuring sensor i.e. load cell. The load cell is an analog type output device.